2012
DOI: 10.1002/asna.201211685
|View full text |Cite
|
Sign up to set email alerts
|

AGN jets under the microscope: A divide?

Abstract: A new paradigm for active galactic jet kinematics has emerged through detailed investigations of BL Lac objects using very long baseline radio interferometry. In this new scheme, most, if not all, jet components appear to remain stationary with respect to the core but show significant non-radial motions. This paper presents results from our kinematic investigation of the jets of a statistically complete sample of radio-loud flat-spectrum active galaxies, focusing on the comparison between the jet kinematic pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Several well-studied AGN have been found to show nonballistic motions in their jets, which are interpreted in terms of a helical or precessing jet (e.g. Steffen et al 1995;Abraham 1999;Britzen et al 2009;Liu et al 2010;Kudryavtseva et al 2011a;Karouzos et al 2012a). The projected positions of individual components on the plane of the sky can be directly used for fitting of analytical models and can therefore usually constrain both the opening angle of the precession cone, the initial time and angle of ejection of each jet component, and given enough data, the periodicity of the jet precession and consequently of the binary black hole system.…”
Section: Agn Jet Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several well-studied AGN have been found to show nonballistic motions in their jets, which are interpreted in terms of a helical or precessing jet (e.g. Steffen et al 1995;Abraham 1999;Britzen et al 2009;Liu et al 2010;Kudryavtseva et al 2011a;Karouzos et al 2012a). The projected positions of individual components on the plane of the sky can be directly used for fitting of analytical models and can therefore usually constrain both the opening angle of the precession cone, the initial time and angle of ejection of each jet component, and given enough data, the periodicity of the jet precession and consequently of the binary black hole system.…”
Section: Agn Jet Kinematicsmentioning
confidence: 99%
“…The jet ridge line of AGN jets can be used to identify jets with strong variations of their curvature along the jet axis. Karouzos et al (2012a), using a simple geometrical model of a helical jet, showed that a helically structured or a precessing jet can give rise to the curvature observed in many AGN jets.…”
Section: Agn Jet Morphologymentioning
confidence: 99%
“…Jet bendings or non-linear morphologies are very common in BL Lacs (e.g. Karouzos et al 2012). Jorstad et al (2005) suggest that the first bending in 3C 66A jet occurs smoothly from 1.2 mas up to 3 mas.…”
Section: Morphologymentioning
confidence: 99%
“…Britzen et al 2001;Tateyama et al 2002;Britzen et al 2005bBritzen et al , 2010; Fractional variability amplitude Fvar for jet components C0, C1, Ca, C2, C4, C8 as function of time in 3-year bins Karouzos et al 2012a)…”
mentioning
confidence: 99%